Insights into refractory chronic inflammatory demyelinating polyneuropathy: a comprehensive real-world study - Zheng, Yongsheng; Hu, Jianian; Sun, Chong; Qiao, Kai; Zhao, Yanyin; Liu, Bingyou; Sun, Jian; Xi, Jianying; Luo, Sushan; Lu, Jiahong; Zhao, Chongbo; Lin, Jie (Frontiers in Neurology, 2024)
Background Refractory chronic inflammatory demyelinating polyneuropathy (CIDP) is a challenging subset of CIDP. It does not respond well to immune therapy and causes substantial disability. A comprehensive understanding of its clinical profile, electrophysiological characteristics and potential risk factors associated with refractoriness remains to be further elucidated. Methods Data in this cross-sectional study was collected and reviewed from the Huashan Peripheral Neuropathy Database (HSPN). Included patients were categorized into refractory CIDP and non-refractory CIDP groups based on treatment response. The clinical and electrophysiological characteristics were compared between refractory and non-refractory CIDP groups. Potential risk factors associated with refractory CIDP were explored with a multivariate logistic regression model. Results Fifty-eight patients with CIDP were included. Four disease course patterns of refractory CIDP are described: a relapsing–remitting form, a stable form, a secondary progressive form and a primary progressive form. Compared to non-refractory CIDP patients, refractory CIDP exhibited a longer disease duration (48.96 ± 33.72 vs. 28.33 ± 13.72 months, p = 0.038) and worse functional impairment (MRC sum score, 46.08 ± 12.69 vs. 52.81 ± 7.34, p = 0.018; mRS, 2.76 ± 0.93 vs. 2.33 ± 0.99, p = 0.082; INCAT, 3.68 ± 1.76 vs. 3.03 ± 2.28, p = 0.056, respectively). Electrophysiological studies further revealed greater axonal impairment (4.15 ± 2.0 vs. 5.94 ± 2.77 mv, p = 0.011, ulnar CMAP) and more severe demyelination (5.56 ± 2.86 vs. 4.18 ± 3.71 ms, p = 0.008, ulnar distal latency, 7.94 ± 5.62 vs. 6.52 ± 6.64 ms, p = 0.035, median distal latency; 30.21 ± 12.59 vs. 37.48 ± 12.44 m/s, p = 0.035, median conduction velocity; 58.66 ± 25.73 vs. 42.30 ± 13.77 ms, p = 0.033, median F-wave latency), compared to non-refractory CIDP. Disease duration was shown to be an independent risk factor for refractory CIDP (p < 0.05, 95%CI [0.007, 0.076]). Conclusion This study provided a comprehensive description of refractory CIDP, addressing its clinical features, classification of clinical course, electrophysiological characteristics, and prognostic factors, effectively elucidating its various aspects. These findings contribute to a better understanding of this challenging subset of CIDP and might be informative for management and treatment strategies.